Proceedings of the Seventh International Conference on Languages and Arts (ICLA 2018) 2019
DOI: 10.2991/icla-18.2019.49
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Direct Corrective Feedback on Students’ Writing of Recount Text

Abstract: The purpose of this research is to determine the effect of direct corrective feedback toward students' writing, especially in writing recount text. This is a quasi-experimental research. The students of grade ten at MAN 3 Payakumbuh were the population of this study. The sample was chosen by using cluster random sampling technique in which there were 38 students as the subjects of this research.Direct corrective feedback was applied in experimental class and indirect corrective feedback was applied in control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Another previous study was done by Susanti and Ayuni (2018) who revealed that the use of Padlet in classroom obtained a possitive response from the students because it is easy to use and more fun and it can help the students increase their writing ability. It is in line with Arifin et al (2019) stating that even though the students have a problem in using this media like limitation internet connection, Padlet is implemented in the teaching and learning process especially in writing classroom during pandemic era.…”
Section: Padletsupporting
confidence: 65%
“…Another previous study was done by Susanti and Ayuni (2018) who revealed that the use of Padlet in classroom obtained a possitive response from the students because it is easy to use and more fun and it can help the students increase their writing ability. It is in line with Arifin et al (2019) stating that even though the students have a problem in using this media like limitation internet connection, Padlet is implemented in the teaching and learning process especially in writing classroom during pandemic era.…”
Section: Padletsupporting
confidence: 65%